Influência da precipitação pluviométrica nas características físicas, química e higiênico-sanitária da água de trés mananciais de abastecimento público. - do Amaral, L. A.; Nader Filho, A.; Rossi Júnior, O. D.; Iaria, S. T. (My University, 1994)
Aiming to know the influence of the pluviometric precipitation over the physical chemical and bacteriological characteristics of the water coming from three sources of public supply, and to verify the probable origin of faecal contamination, tests of total coliforms, faecal coliforms, faecal streptococci and mesophilic microorganisms, as well as the determination of pH, temperature and turbidity of 156 water samples were done. The samples were taken from a stream, a drain and an artesian well, located in the city of Jaboticabal, SP, Brazil. The results obtained showed that the occurrence of pluviometric precipitation determined a significant increase of the number of total coliforms in the water samples from the stream. The use of the ratio CF/EF, indicate the probable origin of the faecal contamination only in the samples of the water coming from the stream, which were defined as being of human origin. In relation to the physical-chemical composition it was noticed that the influence of the pluviometric precipitation over the turbidity appeared to be higher and significant in the samples of water of the stream.
Effect of pluviometric precipitation on the physical, chemical, and health/hygiene aspects of water from three public water supplies
Keywords: fresh water; rain; Brazil; comparative study; Enterobacteriaceae; isolation and purification; microbiology; pH; photometry; Streptococcus; water pollution; water supply; Comparative Study; English Abstract; Fresh Water; Hydrogen-Ion Concentration; Nephelometry and Turbidimetry; Rain; Water Microbiology; Water Pollution; Water Supply